Meta-Analysis: Effectiveness of mHealth Utilization on Antenatal Care - Nuryuliana, Nuryuliana; Demartoto, Argyo; Adriani, Rita Benya (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: An antenatal visit is the presence of pregnant women at health facilities to check their pregnancy and get information about their pregnancy. The use of mobile health interventions (mHealth) such as SMS, voice messages, videos, and interactive mobile phones can provide behavioral support and health education needs of pregnant women. This study aims to determine the effectiveness of the use of mHealth on the improvement of antenatal visits. Subject and Method: Systematic reviews and meta-analyses were conducted using PRISMA guidelines and PICO models which included Population = pregnant women; Intervention= mHealth, Comparison= does not use mHealth; Outcome= antenatal visit. Articles are collected through databases such as Google Scholar, PubMed, BMJ, Plos One, Plos Digital Health, JMIR, JPHIA, HSPRJ, JIO, Journal of Midwifery and Traditional Health. Keywords used: mHealth or Telemedicine or Phone or Mobile Phones or Mobile Telephone or Short Message Service or Whatsapp Group, Antenatal Visite or Antenatal Care or Pregnancy or Pregnant or Prenatal or Mother Health. A total of 13 articles that met the inclusion criteria were meta-analyzed and assessed using RevMan 5.3. Results: Meta-analyses from Tanzania, Kenya, India, Brazil, Peru, Bangladesh, Nigeria, Uganda, and Indonesia showed that pregnant women who used mHealth services were 2.94 times more likely to have antenatal visits compared to not using mHealth and the effect was statistically significant (OR= 2.94; CI95%= 2.19 to 3.94; p <0.001). Conclusion: The use of mHealth may increase antenatal visits.